SAT0448 ATP IS THE SECOND KEY SIGNAL OF GOUT FLARE BESIDES MSU. (June 2019) - Zhang, Hong-Liang; Zhu, Zi-Wen; Tao, Jinhui; Tang, Yu-Jie; Xin-Ya, LI; Lin, LI; Lu, Qun-Qun
Abstract : Background: Gout is an inflammatory disease associated with hyperuricemia and characterized by recurrent arthritis. In previous study, MSU which generated by hyperuricemia was recognized by the toll-like receptor and NOD receptor of the intrinsic immune system, then activated the NALP3 inflammasome to induce the secretion of IL-1 beta, causing gout . However, this mechanism cannot explain why most patients with hyperuricemia do not have gout attacks in clinical practice, suggesting that there may be other pathogenic signals in the flare of gout. Our team previously found that P2X7R might play a key regulatory role in the pathogenesis of gout [1] .What's more, single nucleotide polymorphisms associated with P2X7R function regulate the onset of gouty arthritis [2], suggesting that ATP, as the ligand of P2X7R, may be a second key signal in addition to MSU to stimulate gout attack. Objectives: To understand whether ATP act as a key factor in gout development besides MSU. Methods: The rat hyperuricemia model was prepared by intraperitoneal injection of the uratase inhibitor oxazinic acid. Followed by ATP injection into the tail vein to observe the incidence of arthritis and compared with the Coderre's method-established gouty arthritis [3] . Results: Forty hyperuricemia rats were prepared and 0.5ml ATP (10mM) solution was injected into the tail vein of the rat respectively, about 95% (38 rats) developed spontaneous arthritis. This type of spontaneous arthritis is very different from the Coderre's method in the following aspects: (1) The onset time of spontaneous arthritis is faster. The time of joint swelling in spontaneous arthritis peaked at 6.0 ±2.0 hours after ATP injection, while it took 2 to 3 days for arthritis caused by local injection of MSU to reach its peak. (2) The affected joints were different: The Coderre's method joints swelling only at the MSU injection site. Spontaneous arthritis can involve multiple joints, in which 71% have one joint affected, 21% have two joints affected and 8% with three or more than three joints affected by redness and swelling. (3) Distinct histopathologic characteristic: In Coderre's method, lymphocytes caused by local injection account for about 60%, with fewer neutrophils; In spontaneous arthritis, neutrophils account for more than 90% and lymphocytes are less. (4) Different sources of MSU: there is local MSU in spontaneous arthritis, which is associated with hyperuricemia; the local presence of MSU in Coderre's arthritis was artificially injected. Conclusion: The spontaneous arthritis due to the synergistic effect of ATP and MSU is consistent with the characteristics of human gout arthritis, suggesting that ATP is the key second signal besides MSU to stimulate gout attack. References: [1] Tao JH, Zhang Y, Li XP. P2X7R: A potential key regulator of acute gouty arthritis. Semin Arthritis Rheum. 2013; 43(3): 376-380. [2] Tao JH, Cheng M, Tang JP, et al. Single nucleotide polymorphisms associated with P2X7R function regulate the onset of gouty arthritis. PLoS One. 2017Aug10;12(8):e0181685. [3] CoderreTJ, Wall PD.Ankle joint urate arthritis (AJUA) in rats: An alternative animal model of arthritis to that produced by Freund's adjuvant. Pain. 1987; 28(3):379-93. Acknowledgement: This work was supported by grants from the National Natural Science Foundation of China (81771774) and the Anhui Provincial Natural Science Foundation (1708085MH191) Disclosure of Interests: None declared